Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 98462315 species occurrences available in GBIF matching the query: { "HasCoordinate" : [ "is false" ] } The dataset includes 98462315 records from 14003 constituent datasets: 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 1 records from The tadpoles of Murree Hills Frog Nanorana vicina (Anura: Dicroglossidae). 66 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 12 records from A new genus for the freshwater crab Potamonemus asylos Cumberlidgeı 1993 ı (Brachyura: Potamoidea: Potamonautidae) from Cameroonı Central Africaı with a key to the genera of the Potamonautinae. 8446 records from MEXU/Leguminosae. 7 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 92 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 7 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 1 records from A new name for Dendronephthya kukenthali Gravier, 1908 (Octocorallia, Nephtheidae): Dendronephthya perezi nom. n.. 15 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 3 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2154 records from DBG Physaria bellii Demographic Monitoring. 16 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 500 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 2140 records from Captive Primate Specimens of Japan Monkey Centre. 52873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 30 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 3 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 8 records from A Catalogue and Historical Study of the Odonata of Ecuador. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 49 records from The genus Litophyton Forskål, 1775 (Octocorallia: Alcyonacea: Nephtheidae) from Australia. 3 records from A new fossil species of Pycnomerus Erichson (Coleoptera: Zopheridae) from Baltic amber, and a replacement name for a Recent North American congener. 22736 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 152 records from Fitoplancton de la provincia oceánica del mar Caribe colombiano. Diez años de historia. 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 89 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 23 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 4 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 4 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 3 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 4 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 25 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 6 records from BioAcoustica: Wildlife Sounds Database. 7 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 8 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 29977 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 19 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 4 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 2 records from Two new species of the genus Geckobia Mégnin, 1878 (Acariformes, Prostigmata, Pterygosomatidae) from Peru. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 9 records from Contributions to the knowledge of Atlantic Canadian Histeridae (Coleoptera). 3 records from New species of Alpinalona Alonso & Sinev, 2017 (Cladocera: Anomopoda: Chydoridae) from South-East USA. 3 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 1 records from Nothrus pulverulentus. 1 records from The Indian net-casting spider name Deinopis goalparaensis Tikader & Malhotra is a nomen dubium (Araneae: Deinopidae). 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 74 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 87 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 2 records from Condamine Alliance. 4 records from Mabuia wirzi Roux, 1925 (Squamata: Scincidae), an overlooked synonym of Dasia olivacea Gray, 1839, with notes on the synonymy of Dasia olivacea. 34 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 3 records from A new species and new record of the leafhopper genus Balclutha (Hemiptera: Cicadellidae: Deltocephalinae) from China with key to species. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 1 records from Protozoa ZMK. 10 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 2 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 57 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 44 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 58 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 2 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 33 records from Tardigrad collection of the National Museum of Nature and Science. 6574 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 4 records from Two new species of nematode (Oxyurida, Hystrignathidae) parasites of Passalus interstitialis Escholtz, 1829 (Coleoptera, Passalidae) from Cuba and a new locality for Longior similis Morffe, Garcia & Ventosa, 2009. 6 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 46 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 4550 records from Herbier Louis-Marie (QFA) - Collection de lichens. 98 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 241 records from Amphibian Specimens of the Yamagata Prefectural Museum. 3 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 183 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 444 records from Marsabit Ecosystem Inventory Surveys 2014. 5 records from A new sponge species of the genus Antho (Demospongiae, Microcionidae) from the Tyrrhenian deep Sea. 607514 records from Plant. 4 records from A taxonomic review of the genus Asterostegus (Echinodermata: Ophiuroidea), with the description of a new species. 166 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 6 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 7 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 111 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 1 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 24 records from Chapter 7: Linnaean Plant Names and their Types (part Q). 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 6 records from New ants (Hymenoptera: Formicidae) from Micronesia. 1 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 36 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 5576 records from Colecção Entomológica IIA. 6 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 30070 records from 16S sequencing of environmental samples to test the impact of sediment source. 1 records from Zur Kenntnis der Lithobiiden. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 392 records from MZFC/Coleccion de Aves. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 2 records from Phasmarhabditis bonaquaense n. sp. (Nematoda: Rhabditidae), a new slug-parasitic nematode from the Czech Republic. 307 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 1 records from Données naturalistes de Ségolène FAUSTEN. 8 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras (Oeceoclades_bonampak). 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 1 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 15241 records from Natural History Museum Maastricht (NL) - Herbarium. 6077 records from DMNS Egg Collection (Arctos). 20 records from MZL Invertebrate Collections. 5 records from New look on the geographical variation in Rhinolophus clivosus with description of a new horseshoe bat species from Cyrenaica, Libya. 1303 records from Crustacean specimens of Bihoro Museum. 241 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 17 records from New genus and species of cockroaches from the tribe Brachycolini (Blattaria Blaberidae: Blaberinae) and redescription of the Hormetica strumosa. 1720 records from Lepidopterous specimens of Yamagata Prefectural Museum. 2 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 9 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 3159 records from Collection of Coleoptera. 345 records from données arachnologique de LEUCHTMANN Maxime. 52 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 2 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 5 records from Ostracods (Crustacea) associated with microbialites across the Permian-Triassic boundary in Dajiang (Guizhou Province, South China). 214 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 6 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 300 records from Orthoptera - SMF. 213 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 34 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 1 records from Wrong side of the leaf: assigning some Lithocolletinae species (Lepidoptera: Gracillariidae) to their proper genera. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Ensemble des données Rhopalocères. 4 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 26 records from An updated checklist of aquatic plants of Myanmar and Thailand. 18 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 750 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 6 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 50419 records from University of Michigan Museum of Paleontology - Vertebrates. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 1 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 1 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 137556 records from Queensland Museum provider for OZCAM. 9 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 4 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 8927 records from Herbarium Universitatis Daugavpiliensis. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 80 records from Colección de Entomología - Curculionidae. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 5 records from Universidad del Valle de Guatemala - Colección de Artrópodos. 1 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 113 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 100 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 1 records from Données de la naturaliste Laurence Beauchamp. 3098 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 269 records from Collections ichtyologiques et herpétologiques (BOUM). 1494 records from MCP-Mamiferos - Coleção de Mamíferos. 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 125 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 12 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 55 records from Temporary expansion to shelf depths rather than an onshore-offshore trend: the shallow-water rise and demise of the modern deep-sea brittle star family Ophiacanthidae (Echinodermata: Ophiuroidea). 73 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 1 records from Norwegian Lepidoptera working group. 8 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 7 records from New biogeographical makeup for colonisation of the Baja California Peninsulaı with the description of a new Onthophagus (Coleoptera: Scarabaeidae: Scarabaeinae). 9 records from Occurrence database of native plants and animals of south-central Chile. 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 1 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 3 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 1 records from Archaeomalthus - (Coleoptera, Archostemata) a ‘ ghost adult ’ of Micromalthidae from Upper Permian deposits of Siberia?. 1 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 11 records from On the Bennelongia nimala and B. triangulata lineages (Crustacea, Ostracoda) in Western Australia, with the description of six new species. 466 records from PSU-Seagrass Collection. 7 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 14 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 270 records from bmhs_weatherheadshell_collection. 598 records from Entomological collection of the National Museum. 1 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1 records from Miriapodi di alcune grotte della Campania. 1 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 1 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 1 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 13 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 27 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 6 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 1212 records from BES pyrosequencing. 105 records from Living Cirripedia. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 2 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 154 records from Helmintos parásitos de peces del sureste de México. 7 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 14 records from Two new free-living nematode species of Setosabatieria (Comesomatidea) from the East China Sea and the Chukchi Sea. 10 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 35 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 4 records from Land and freshwater molluscs of Northern Spain. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 47 records from Carpoteca de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 3 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 7 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 6 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 5 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 1 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 134 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 9 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 1750 records from University of California Santa Barbara Invertebrate Zoology Collection. 3 records from Données naturalistes de Hubert GUIMIER. 53 records from Données naturalistes de Hervé BOUYON. 7 records from Données de la collection Rousset -1947-2013. 6 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhingidae. 3 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 88 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 812 records from Entomology Collection at the Natural History Museum of Utah. 3 records from Three new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) from Taiwan. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 930 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 4 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 1 records from An interesting new genus of Berothinae (Neuroptera: Berothidae) from the early Eocene Green River Formation, Colorado. 1 records from Colección Herpetológica de la Patagonia. 4 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 1 records from Description of a new species of genus Trachischium with a redescription of Trachischium fuscum (Serpentes: Colubridae: Natricinae). 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 33280 records from ALCB - Herbário Alexandre Leal Costa. 3175 records from Herbarium specimens of Limoges university (LIMO). 1097 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 44113 records from Fish specimens of Kagoshima University Museum. 2268 records from Amplicon sequencing of gyrA and parC in Escherichia communities in river/lake sediments. 9819 records from UTEP Invertebrates (Arctos). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 75 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 738 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 19 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 5 records from A new species of Enosis Mabille, 1889 (Lepidoptera, Hesperiidae, Hesperiinae) from southern Brazil and notes on Enosis angularis (Möschler, 1877). 1 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 998 records from Korean Ethnobotany Database. 10 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 488 records from Weed and native flora data for the Swan Coastal Plain. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 327 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 14 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 908 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 1148 records from Analysis of plasmidome of high-altitude lakes from the Andean Puna. 878 records from COA Bird Collection (Arctos). 9 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 3 records from Distoseptispora bambusae sp. nov. (Distoseptisporaceae) on bamboo from China and Thailand. 10654 records from Bryophyte specimens of The Nagoya University Museum. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 9949 records from University of Guam Insect Collection. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 47 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 2 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 6 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 196 records from Collection des mammifères d'Auvergne. 6 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 8 records from Report on a collection of dragonflies (Odonata) from the Andaman Islands.. 8 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 2731 records from Museu de Ciències Naturals de Barcelona: BGJBB. 1 records from The identity of Parandra laevis Latreille, 1804 and nomenclatural changes in the Parandrinae (Coleoptera, Cerambycidae). 7 records from Morphologische Daten von Natrix. 7 records from Taxonomic revision of the epigean representatives of the spider subfamily Harpacteinae (Araneae: Dysderidae) on the island of Crete. 1 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 1 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 4 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 8 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 15 records from Collection botanique Lamy de la Chapelle E. (BOUM). 183 records from Brown University Herbarium. 1 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 22 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 9 records from Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae). 1411 records from MCP-Aves - Coleção de Aves. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 74 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 57 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 8 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 6007 records from LISU Herbario Angola. 45 records from Bird specimens of Saitama Museum of Natural History. 11 records from orthopteracollections-nhmj-ioj. 4435 records from CNAC/Coleccion Nacional de Acaros. 2 records from Carnivores of Syria. 2 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 1 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 7 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 359 records from Collections of Bioclass, school #179, Moscow. 3 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 1217 records from 16S rRNA metagenomic investigation of arsenotrophic bacteriome of ground water and soil from arsenic-prone area of Bangladesh. 24370 records from Muséum d'Avignon. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 1333 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 29 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 1591 records from CNIN/Abejas de México/Apoidea. 1 records from RNF - Données du Parc Naturel Régional du Vercors. 889 records from 16S rRNA gene pyrosequencing and clone library revealed highly diverse microbial communities in natural marine biofilms. 197 records from Flora útil del Municipio de la Huerta, Jalisco. 30 records from Insectes Hyménoptères Scollidés de France. 2 records from Description of a new brachypterous scarab species, Orphnus brevialatus (Coleoptera: Scarabaeidae: Orphninae) from East Africa, with notes on flightlessness in the orphnines. 859 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 1 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 228 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 2 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 14 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 10 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 13 records from A new South American species of Banasa Stål (Hemiptera: Heteroptera: Pentatomidae: Pentatominae): from egg to adult. 4 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 1338 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 195 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 28 records from Contribution to the knowledge of the genus Cordilura Fallén (Diptera, Scathophagidae) from Japan, with descriptions of three new species. 18 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 5 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 192 records from PeECE II - Pelagic Ecosystem CO2 Enrichment Study, Raunefjord, Bergen, Norway. 54 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 16797 records from University of Minnesota Insect Collection. 2860 records from ARABEL - Arachnologia Belgica. 87 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 10 records from Catalogue of Ampulicidae, Crabronidae and Sphecidae of Iran (Hymenoptera, Apoidea). 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 1 records from Seven new species of Night Frogs (Anura, Nyctibatrachidae) from the Western Ghats Biodiversity Hotspot of India, with remarkably high diversity of diminutive forms. 1839 records from MLZ Bird Collection (Arctos). 2 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 21 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 25 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2421 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Tanacetum vulgare dominated forb vegetation. 21 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 3 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 4976 records from Gastropod Specimens of the Yamagata Prefectural Museum. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 2 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 1098 records from Butterflies_of_Singapore_and_Peninsular_Malaysia_(Nymphalidae). 281 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 5 records from UWYMV Herpetology Collection (Arctos). 4585 records from Marine bacteria Targeted Locus (Loci). 43567 records from FUEL - Herbário da Universidade Estadual de Londrina. 1 records from Eine Milbendiagnose aus dem Nachlass Dr. Josef Schweizer. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 120430 records from Dataflos. 2 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 163 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 47133 records from Herbarium Senckenbergianum (FR) - Fungi. 6 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 2 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 4 records from A new scale insect host family (Hemiptera: Asterolecaniidae) for Aphytis (Hymenoptera: Aphelinidae) in China. 250 records from Plant specimens of Bihoro Museum. 4 records from Is Copytus Skogsberg, 1939 (Crustacea: Ostracoda) a neocytherideid? With description of a new family and two new species. 8 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 4 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 214 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 2 records from Two new species of Spider Wasps (Hymenoptera, Pompilidae), Ctenagenia pagliano from Lebanon and Evagetes liane from Canary Islands. 2 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 69 records from The Amphibians of the Mitaraka massif, French Guiana. 4 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 943 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 9 records from First report of the old world genus Pelecystola in North America, with description of a new species (Lepidoptera, Tineidae). 8 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 2980 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 251 records from Institut Mediterrani d'Estudis Avançats (CSIC-UIB): IMEDEA-OTO. 4 records from Descriptions of two new Vietomartyria species (Lepidoptera, Micropterigidae) from China. 343 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 31658 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 4 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 77 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 57 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 21 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 393 records from Reptilia ZMK. 1 records from Xibalbanus cozumelensis, a new species of Remipedia (Crustacea) from Cozumel, Mexico, and a molecular phylogeny of Xibalbanus on the Yucatán Peninsula. 1383 records from Plant observations from Białowieża National Park. 191 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 7 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 1 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 48 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 1 records from Pauximyia, a new genus of Odiniidae (Diptera: Acalyptratae) with description of two new species from Brazil. 1 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 21 records from Characterization of Microbial Community Structure and Population Dynamics of Tetrachloroethene-Dechlorinating Tidal Mudflat Communities using a Multipronged Approach. 1 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 598 records from Inventario de Hymenóptera; parasítica en México. 3 records from Fourth note on the Dinosauria of the Laramie.. 35 records from New records of Chalcidoidea (Hymenoptera) from the Maltese Islands with an updated checklist. 23 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 12888 records from MfN - Fossil Fish Collection. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 4 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 882 records from Ibaraki Nature Museum, Fungi collection. 307 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 13 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 35 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 94 records from Révision du genre Danuriella Westwood, 1889 (Mantodea). 384 records from Saltern microbial community diversity. 797 records from Variable Loading Conditions Influence Charge and Current Generation in Multi-Anode Environmental Microbial Fuel Cells. 275 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 44 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 1 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 18 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 1392 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 5 records from Intertidal Euryleptid polyclads and description of a new Stylostomum Lang, 1884 from Maharashtra, India. 16 records from The types of skippers described by Shu-Iti Murayama (Lepidoptera: Hesperiidae). 62 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 10 records from Inventaire de la flore de Lot-et-Garonne 2017. 15 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 3298 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 9 records from New species of Hercostomus Loew, 1857 from Afrotropics (Diptera: Dolichopodidae) and key to Afrotropical fauna. 136 records from Lucanidae. 4579 records from Estación Biológica de Doñana - CSIC, Anfibios. 33 records from R. L. McGregor Herbarium Lichen Collection. 17 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 2 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 24 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 2 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 60 records from Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae Lamiinae) with erect setae on elytral surface. 200 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 18 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 4 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 15 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 3 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 141 records from Swan Coastal Plain Survey. 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 5 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 94 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 12 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 20 records from NZCS Brownsberg Nature Park Monitoring. 141 records from Review of the genus Paramesius Westwood, 1832 (Hymenoptera: Diapriidae, Spilomicrini) from Russia, with description of four new species. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 8 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 1 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 6 records from COI mtDNA barcoding and morphology for species delimitation in the spider genus Ixchela Huber (Araneae: Pholcidae), with the description of two new species from Mexico. 8 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 2184 records from Spatial variation of bacterioplankton in south Atlantic Bight. 66 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 1 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 5 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 1238 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 60 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 5 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 199 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 17051 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 7 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 7 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 1 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 99 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 892 records from (UTC) University of Tennessee Mammals Collection. 1151 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF ARRAIAL DO CABO - BRAZIL. 5631 records from Birds Specimens. 2 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 1952 records from ISM Ichthyology Collection. 26 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 2424 records from DMNS Mammal Collection (Arctos). 14 records from Données naturalistes de Quentin ROME. 4 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 5 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 1 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 467 records from IBF Monitoring of Fungi. 33 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 4713 records from The Himalayan Uplands Plant database (HUP Version 1). 11 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 10 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 275 records from National Museum of Natural Science. 23 records from A key to the species of Protogamasellus (Acari: Ascidae), with a new species from the Brazilian Pantanal. 7988 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 28 records from Face Biting on a Juvenile Tyrannosaurid and Behavioral Implications. 14 records from First record of the genus Dictyopharina Melichar, 1903 (Hemiptera: Fulgoroidea: Dictyopharidae) from China, with descriptions of two new species. 26 records from Results of a recent bat survey in Upper Myanmar including new records from the Kachin forests. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 103 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 973 records from Global Ocean Sampling Expedition. 1 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 149 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 1 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1575 records from Hermatypic Corals of Western Australia. 239416 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 9 records from Hybrizontinae (Hymenoptera, Ichneumonidae), a new subfamily for the fauna of Turkey. 2 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 132 records from Birds Specimens of Akita Prefectural Museum. 945 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 1383 records from UAM Fish Collection (Arctos). 2 records from Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. 1 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 3 records from Rideriana amazonica gen. nov. and sp. nov. of Pentatomini (Heteroptera, Pentatomidae). 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 1 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 1 records from Données naturalistes de LE GLOANEC Vincent. 26800 records from MSUM Ichthyology and Herpetology Collections. 1 records from Juvenile eucladid crinoid from the Middle Devonian of Turkey. 36 records from Bird Specimens of The Cattle Museum. 1 records from -- First- - description -- of- - the- - male- - of- - Dendrothrips karnyi (Thysanoptera, -- Thripidae) - from- - Iran. 16809 records from Genebank, National Institute of Agrobiological Sciences. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 407 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 2333 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 23 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 5 records from An overview of the genus Plesionika Bate, 1888 (Decapoda, Caridea, Pandalidae) in Asian waters. 111 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 2 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 3 records from Flora Atlas N.T.. 23 records from Fishes in the Argentine Sea from 1967 to the present time. 12 records from Newly recorded leafhoppers of the subfamily Cicadellinae (Hemiptera: Cicadellidae) with description of a new species from Pakistan. 1597 records from Herbario COFC de la Universidad de Córdoba: colección histórica. 51 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 455 records from WOLL AVH data. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 46 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 2 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 5 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 8 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 16 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 10 records from REVISÃO DO GÊNERO “ LEPTOCYSTA ” STAL (Hemiptera, Tingidae). 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 8 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 4 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 912 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 4 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 42 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 65 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 3681 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 1 records from Descriptions of new Genera and Species of Odonata in the Collection of the British Museum, chiefly from Africa.. 176 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 2 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 5 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 5 records from Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini). 1 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 4214 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 1 records from A new genus and species of burrower bugs (Heteroptera: Cydnidae) from the mid-Cretaceous Burmese amber. 1 records from Review of the Australian Signal Flies of the Genus Microepicausta (Diptera: Platystomatidae). 13342 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 34 records from Coléoptères Silphidés du département du Loiret. 234 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 8 records from Revision of the Western Palae arctic species of the genus Casinaria H (Hymenoptera, Ichneumonidae, Campopleginae). 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 36 records from Formidabel; Belgian Ants Database. 2568 records from Fish (NHMK-PI). 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 5 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 6 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 145 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 2 records from A new species of Globicornis Latreille (Coleoptera: Dermestidae) from Baltic amber, with a key to fossil species. 6 records from A revision of the genus Zyras (Zyras) Stephens, 1835 (Coleoptera, Staphylinidae, Aleocharinae). I. Current classification status and the redefinition of the genus. 3 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 91752 records from CAS Invertebrate Zoology (IZ). 1 records from A new African Apiocera species (Apioceridae, Diptera). 5917 records from Antimony contaminated sediments Raw sequence reads. 4 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 19 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 26 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 66 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 196 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 724 records from There are 3 zooplankton samples from 3 different ponds, we collected sample and use the fresh samples to do DNA extraction directly, then mix them with adjustment guided by the number of species within each of them. At last, use Hiseq-2599 PE-150 to do NGS work. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 3 records from Insects, Outer Hebrides. 16 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 20 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 2 records from A New Genus And Species Of Panaphantina (Coleoptera: Staphylinidae: Pselaphinae: Euplectitae: Trichonychini) From Australia. 4 records from Two new species of heavily calcified cyclostome bryozoans from the intertidal of Akkeshi Bay, Hokkaido, Japan. 1271 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 20 records from A new leafhopper genus Discolopeus and nine new species (Hemiptera, Cicadellidae, Deltocephalinae) associated with shrubs, trees and poisonous plants in South Africa. 19 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 223 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 31 records from Skull anatomy and phylogenetic assessment of a large specimen of Ecteniniidae (Eucynodontia: Probainognathia) from the Upper Triassic of southern Brazil. 8 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A new tyrannosaurine (Theropoda: Tyrannosauridae) from the Campanian Foremost Formation of Alberta, Canada, provides insight into the evolution and biogeography of tyrannosaurids. 30 records from The first species of Cotithene Voss (Coleoptera: Curculionidae: Curculioninae) from Amazonian Brazil, with notes on its role as a pollinator of Evodianthus funifer (Poit.) Lindm. (Cyclanthaceae). 2176 records from NSW South Coast & ACT plants. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 8 records from Ascidians collected during the Madibenthos expedition in Martinique: 2. Stolidobranchia, Styelidae. 1 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 342 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 32438 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 865 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 17 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 5 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 8608 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 1375 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 31 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 28 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 177 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 1 records from Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region. 80 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 51 records from Colección de Aráceas del Jardín Botánico San Jorge. 1247 records from Weeds Australia. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 1 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 4 records from Brown algae specimens of Komatsu City Museum. 12147 records from Danish Ants (Formicidae). 1 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 3 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 51 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 70 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 3340 records from Palaeobiology collection, FAU Erlangen. 23928 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 500 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 6 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 500 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 3537 records from ATCC Bacteria Collection Catalog. 1 records from Hemichordata collection of National Museum of Nature and Science. 2067 records from The Broward College Insect Collection. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 6 records from Description of Harpactea popovi sp. n. from Bulgaria with further taxonomic notes on related species (Araneae, Dysderidae). 122 records from Colección de Líquenes Austroamericanos Ex Herbario Regnelliano- FML. 25973 records from Berea College, Ralph L. Thompson Herbarium. 54 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 4 records from Ecosphère_2017_12_18. 3392 records from Fish specimens of Toyama Science Museum. 2 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 5 records from Anderemaeus (Acari, Oribatida) - overview, three new species from South America and reassessment of Anderemaeidae supported by ontogeny. 19 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 3 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 1 records from Current status of the non-indigenous molluscs in Chile, with the first record of Otala punctata (Müller, 1774) (Gastropoda: Helicidae) in the country and new records for Cornu aspersum (Müller, 1774) and Deroceras laeve (Müller, 1774). 156 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 7012 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 40358 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 376 records from Données naturalistes de LUPOLI Roland. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 1 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 2353 records from Weber State University Herbarium. 1 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 1 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 3 records from Données naturalistes de François BRETON. 2 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 1 records from A new stenochirid lobster (Crustacea, Decapoda, Stenochiridae) from the Early Jurassic of France. 27108 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 95 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 1 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 120 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 3 records from The Mastigitae genus † Baltostigus in Upper Eocene Rovno amber (Coleoptera: Staphylinidae: Scydmaeninae). 1723 records from Tucurui_Metagenoma_MGRAST. 10 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 29996 records from Lepidoptera specimen database of Japan. 21 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 7 records from A review of fossil Bursidae and their use for phylogeny calibration. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 23677 records from Collection Vermes - ZMB. 1610 records from Culture Collection of Algae. 4 records from SIM-Fungal records compiled by Joan Montón. 6 records from Nueva especie de Aleuropleurocelus Drews y Sampson (Hemiptera: Aleyrodidae) y clave para especies del grupo de forma oval. 36935 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 6 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 45 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 5403 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Description of a new genus and two new species of Forsteriini Tippmann, 1960 from Peru (Coleoptera, Cerambycidae, Lamiinae). 4 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 64 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 1 records from Glossostyles perspicua gen. et sp. nov. and other fungivorous Cecidomyiidae (Diptera) new to the Czech and Slovak Republics. 25 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 3 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 1 records from Inventaire de la flore du Grand Poitiers 2009. 52 records from M. Gollop Collection. 53261 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 698 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 1 records from Berlese's Primitive Oribatid Mites. 200 records from Chapter 7: Linnaean Plant Names and their Types (part O). 1 records from Society Islands beach bum black flies (Diptera: Simuliidae). 8 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 3 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 1 records from A new species of Andinobates (Anura: Dendrobatidae) from the Urabá region of Colombia. 11 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 30 records from NatureMap Calcrete Survey. 137 records from Colección Ficológica del Herbario Criptogámico de la FML. 5 records from A review of Bennelongia De Deckker & McKenzie, 1981 (Crustacea, Ostracoda) species from eastern Australia with the description of three new species. 1508 records from natagora-earlybirds. 306 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 862 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 5 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 41 records from Annotated catalogue of the click-beetle tribe Senodoniini (Coleoptera: Elateridae: Dendrometrinae). 2 records from Macrocyrtus imomzodai Barševskis, 2016, a new synonym of Metapocyrtus (Orthocyrtus) orbiferoides Schultze, 1918 (Coleoptera: Curculionidae: Entiminae). 6 records from Reptiles Specimens of Akita Prefectural Museum. 1 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 7 records from Taphonomy and environment of deposition of a juvenile tyrannosaurid skeleton from the Hell Creek Formation (latest Maastridhtian) of southeastern Montana. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 2 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 1 records from UWIZM Snakes. 13 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 175 records from Type material of land snails (Mollusca: Gastropoda) described from New Zealand by taxonomists in Europe and North America between 1830 and 1934, and the history of research on the New Zealand land snail fauna from 1824 to 1917. 15 records from Conringia orientalis. 4 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 374 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF GORGONA ISLAND. 9 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 5 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 5 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 44 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 6 records from Deep-sea ascidians from Papua New Guinea. 54 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 975046 records from NatureServe Network Species Occurrence Data. 5 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 10 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 1212 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 1 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 1 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 14 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 3 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 4 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 11 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 29 records from On the morphology of the astragalus and calcaneus of the amphicyonids (Carnivora, Mammalia) from the Paleogene of Europe: implications for the ecology of the European bear-dogs. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 30 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 3 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 5 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 40 records from Seawater carbonate chemistry and boron incorporation of planktic foraminifer Orbulina universa during experiments, 2011. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 132 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 8 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 469 records from K-State Museum of Entomological and Prairie Arthropod Research. 1 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 80 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 3 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 24523 records from European Moth Nights. 7 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 4 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 159 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 1 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 91 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 686 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 24795 records from Université d'Aix-Marseille. 3 records from MfN - Micropaleontology. 19 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 6 records from Birds and plant species near Petushki town (Vladimir region). 34 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 386 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 9 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 3 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 86 records from UWYMV Bird Collection (Arctos). 1 records from Données naturalistes de Monsieur JOURDE Rémi. 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 1 records from Synopsis of the extinct Batrachia, Reptilia and Aves of North America. 13458 records from inatura - Erlebnis Naturschau Dornbirn. 3 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 2020 records from Birds (NHMK-BI). 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 139689 records from PlutoF platform observations. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 1 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 8 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 1 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 221 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 2 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 107580 records from Database of invertebrates collected in Mongolia. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 24 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 32916 records from Insect specimen database of Atsugi City Museum. 71 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 356 records from Morphologische Daten von Puffinus creatopus. 2 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 116689 records from South Australian Museum Australia provider for OZCAM. 23 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 148 records from Herbarium BSG Hepaticopsida. 9 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 93 records from Whicher Scarp Flora Survey. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 1 records from Diverse mechanisms of feeding and movement in Cyclorrhaphan larvae (Diptera). 299 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 26 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 54 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 67 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 37 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 8 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 3 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 200 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 25884 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 17 records from Surface samples of the NW Pacific Ocean Targeted Locus (Loci). 3422 records from Tasmanian Museum and Art Gallery provider for OZCAM. 30 records from TTRS Mammals. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 1001 records from Mushroom (KIDR-MR). 9 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 27 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 2 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 207 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 639 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 83 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 5189 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2863 records from University of Sindh Jamshoro Herbarium. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 19 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 246 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 9 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 14 records from A reappraisal of the California Roach / Hitch (Cypriniformes, Cyprinidae, Hesperoleucus / Lavinia) species complex. 4871 records from hymenoptera. 115434 records from Naturalis Biodiversity Center (NL) - Crustacea. 329 records from Amphibian and Reptilian (KIEE-AR). 25 records from Données de NICOLAS Vincent (SAPROX). 8 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 29 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 7 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 4 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 9329 records from Centre de Ressources Biologiques de l'Institut Pasteur. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 3145 records from PCE/TCE dechlorinating microbial community and dehalogenase genes from Wonju Stream, South Korea. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 783 records from Banded Iron Formation and Greenstone survey data. 1 records from Great Eastern Ranges - Slopes to Summit. 17002 records from UCM Mammal Collection (Arctos). 1 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 10 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 2911 records from Tiroler Landesmuseum Ferdinandeum. 47 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 4 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 32 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 197293 records from Natural History Museum, Vienna - Herbarium W. 78 records from Mammals (GNHM-MM). 3 records from Description of Walkeriella miraculosa, gen. n. et sp. n. from South-East Peru (Lepidoptera: Hepialoidea: Hepialidae). 2 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 46647 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 2 records from The first Cacomorphocerus species (Coleoptera, Cantharidae) from Rovno amber a second species of the genus with 11 - segmented antennae. 3 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 9 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 44765 records from Arizona State University Vascular Plant Herbarium. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 6 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 3 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 3 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 2 records from Fungi Collection. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 3 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 1 records from Contribution to the knowledge of the Neotropical canopy dwelling genus Onorius (Coleopteraı Scarabaeidaeı Orphninae): another species from southern Ecuador and notes on the hind gut morphology in the Orphninae. 1 records from Thirteen new records of ferns from Brazil. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 519 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 199037 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 6 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 1 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 139 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 19 records from Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species. 9321 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 4649 records from NE AVH data. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 5 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 13 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 4 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 36 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 27 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 1864 records from Données Entomologiques A. HORELLOU 1988-2018. 1 records from A new species of planthopper in the genus Haplaxius (Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) on palms in Costa Rica and a new country record for Haplaxius skarphion. 6 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 4 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 8 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 65 records from 2019_NSMK_PL. 7207 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 23 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 563 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 32 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 176 records from Herbier National de Guinée (HNG). 59 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 4 records from NZCS Paloemeu River - Grensgebergte Mountains Expedition Conservation International RAP 2012. 6 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 14 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 13 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 54 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 5 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 77 records from Incorporation of Mg and Sr in calcite of cultured benthic foraminifera (Heterostegina depressa and Ammonia tepida) and seawater carbonate chemistry, 2010. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna” (Reptiles y anfibios). 1 records from Hoplophora ardua. 1 records from Memecylon pseudomegacarpum M. Hughes (Melastomataceae), a new species of tree from Peninsular Malaysia. 3 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 2 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 6 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 10 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 2 records from A new species of the assassin bug genus Rihirbus (Hemiptera: Heteroptera Reduviidae) from Vietnam. 1 records from Redescription of Favognathus insularis (Luxton) (Acari: Trombidiformes: Cryptognathidae) from Brazil, with a key to the world species of Favognathus. 22 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 28 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 8 records from Taxonomy and diversity of coelobite bryozoans from drift coral cobbles on Co To Island, northern Vietnam. 34 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 10 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 78 records from Données de VINCENT Alexis (SAPROX). 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 7224 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 6 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 36 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 81 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1121 records from USAC Mammals Collection. 3 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 19 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 47 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 4000 records from Fossil Specimens of Komatsu City Museum. 6 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 2 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 363 records from PSUZC-Reptile Collection. 63 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 38 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 43 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 94 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 2201 records from Collection Echinodermata SMF. 12 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 36706 records from MfN - Fossil vertebrates IV. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 6 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 1828 records from MEXU/Flora de Oaxaca. 11834 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 73 records from Amphibiens et Reptiles de France (Enquête 2). 9 records from Notes on Oriental Clivinini and the description of two new species (Coleoptera: Carabidae: Clivinini). 9304 records from Echinoderm collection of National Museum of Nature and Science. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 109176 records from Herps Specimens. 11457 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 6 records from Données opportunistes. 1 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 440 records from Données de la flore d’Alsace (SBA). 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 16 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 3 records from Two new Afrotropical genera of Scatopsidae (Diptera). 4 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 58 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 289 records from bmhs_butterfly_collection. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 2 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 172 records from checklist-of-birds-of-zomba-mountain. 355 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 998 records from Plant of Folklore (KIDR-PL). 9 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 1110 records from MfN - Fossil plants (Paleophytic). 46178 records from EAC - Herbário Prisco Bezerra. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 32 records from Leif Richardson Vermont Bee Specimens. 183 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 19177 records from Collection Crustacea - ZMB. 1 records from A gall mite, Aceria rhodiolae (Acari: Eriophyidae), altering the phytochemistry of a medicinal plant, Rhodiola rosea (Crassulaceae), in the Canadian Arctic. 2 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 5 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 167 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 5 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 4 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 5 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 49 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 2 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 10 records from Dermaptera in the icipe collection. 138 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 8 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 65 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 6 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 109 records from MMFR Zingiberaceae Botanical. 9 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 2 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 42 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 10 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1098 records from What bug is that. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 1 records from Cretessenia roccamenaica nov. sp. (Acari: Prostigmata: Chyzeriidae: Chyzeriinae) from Sicily, Italy. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 2867 records from Pollichia Pilzherbar. 375 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 4 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 112 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 6 records from Données de l'Observatoire de la Faune de Bourgogne. 8 records from Revision of the types of species of Alloxysta described by Cameron and Fergusson (Hymenoptera: Figitidae: Charipinae) and deposited in the Natural History Museum (London), including a key to the fauna of Great Britain. 58 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 14 records from Review of the leafhopper genus Longicornus Li & Song (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species. 83 records from Wild bees of Belgium. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 73 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 34 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 4 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 44 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 291 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 5420 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 4 records from Aspilanta new genus (Heliozelidae) specimen data. 1 records from Patterns of head shape and scutellation in Drymarchon couperi (Squamata: Colubridae) reveal a single species. 1 records from Echinoderms from the Seaflower Biosphere Reserve. 5 records from On the types species of the New World dung beetle genus Canthidium Erichson, 1847 (Coleoptera: Scarabaeidae: Scarabaeinae), with an annotated checklist of species. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 26 records from Orthoptera (Tettigoniidae and Acridoidea) from Miombo woodlands of Central Tanzania with the description of new taxa. 33 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 123 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 651 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 20 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 123881 records from Allan Herbarium (CHR). 200195 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 50 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Plantas Tapachula). 3 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 69 records from Royal British Columbia Museum Entomology Collection. 112 records from Taxonomic revision of West African cone snails (Gastropoda: Conidae) based upon mitogenomic studies: implications for conservation. 25 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 1 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 7 records from The first elateroid beetles (Coleoptera: Polyphaga: Elateroidea) from the Upper Jurassic of Australia. 208 records from Chapter 7: Linnaean Plant Names and their Types (part V). 356 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 6 records from Four new species and new records of the Neotropical genus Alloraphes Franz (Coleoptera: Staphylinidae: Scydmaeninae). 3 records from MVZ Herp Observations (Arctos). 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 29 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 477 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 5 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 27 records from Eight new Lepadellidae (Rotifera, Monogononta) from the Congo bring to level endemism in Africa’s rotifers. 49 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 2 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 20 records from Colección Entomológica CDMB. 1041 records from NZCS Invertebrates New Collection After 1987. 1 records from A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from Borneo. 3743 records from Uncultured eukaryotes Targeted Locus (Loci). 3 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 1532 records from Restauración y conservación de Isla Guadalupe. 4 records from Lepidoptera (Specimens NRM). 382 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 108 records from Colección nacional de palmas de Colombia - JBQ. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 25 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 21032 records from Marie-Victorin Herbarium (MT) - Bryophytes. 32 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 80 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 11 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 1541 records from Utah State University, Intermountain Herbarium. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 223486 records from Phytochorologie des départements français. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 9902 records from DSMZ Bacteria. 186361 records from CAS Entomology (ENT). 464 records from Carnet B Lorraine. 90762 records from Naturalis Biodiversity Center (NL) - Pisces. 5 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 20 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 59 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 17 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 16 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 11028 records from Collection Trichoptera - SMF. 5 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 103 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 62 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 564 records from Arizona State University Hasbrouck Insect Collection. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 429 records from Collection Strepsiptera SMF. 2 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 22 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 3817 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 4 records from Lista florística de la Costa Grande del estado de Guerrero. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 1 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 15 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 10 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 2 records from Gladiopycnodontidae, a new family of pycnodontiform fishes from the Late Cretaceous of Lebanon, with the description of three genera. 2 records from Two new pill millipedes (Diplopoda: Glomerida: Glomeridae) from high mountains of Vietnam. 2858 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 9 records from Five new species of the genus Noeetomima Enderlein (Diptera: Lauxaniidae) from China, with a key to world species. 7191 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 18 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 4698 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 87 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 40 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 14 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 1 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 59 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 1 records from Notes on and key to the genus Phengaris (s. str.) (Lepidoptera, Lycaenidae) from mainland China with description of a new species. 2786 records from Plan de vertebrados de la Patagonia. 10 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 13 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 2 records from Myzostoma khanhkhoaensis (Myzostomida), a new myzostomid species from the Nhatrang Bay, Vietnam. 2941 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 3 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 32 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 232661 records from Oklahoma Vascular Plants Database Provider. 19 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 5 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 11463 records from Liste des pays par taxon spécimen TOGO. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 12 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 839 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 4 records from Tortonian teleost otoliths from northern Italy: taxonomic synthesis and stratigraphic significance. 1 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 116 records from Collection Ephemeroptera - SMF. 9 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 18 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 3821 records from Denver Museum of Nature & Science - Entomology. 9 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 20261 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 6 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 8 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 7625 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 1 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 1069 records from Characteristics of eukaryotic plankton community in the Coastal Waters of Rongcheng by Illumina sequencing. 6539 records from Spider (NSMK-SP). 26484 records from OUPR - Herbário "Professor José Badini". 47 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 97 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 100 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 5 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 7 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 1 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 21 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 1 records from Amoeboid protists isolated from ancient Siberian permafrost. 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 1 records from The fossil crown wasp Electrostephanus petiolatus Brues in Baltic Amber (Hymenoptera, Stephanidae): designation of a neotype, revised classification, and a key to amber Stephanidae. 188 records from données aranéologiques de CORNIC Jean-François. 419 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 8 records from Données taxonomiques et éthologiques nouvelles sur quatre espèces de Cigales du Sud thaïlandais (Rhynchota, Cicadoidea, Cicadidae). 4 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 1 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 884 records from Sea shells of New South Wales. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 303 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 11 records from Late Cretaceous dinosaurs from the Denver Basin, Colorado. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 1 records from Herpetofauna laguna El Tinije. 3 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 194 records from Ontario Breeding Bird Atlas 1981-1985. 2 records from Holorchis castex n. sp. (Digenea: Lepocreadiidae) from the painted sweet-lips Diagramma pictum (Thunberg, 1792) (Perciformes: Haemulidae) from New Caledonia. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 33 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 2300 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 28 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 1014 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 6 records from Pristipomoides amoenus (Snyder 1911), a valid species of jobfish (Pisces, Lutjanidae), with comparisons to P. argyrogrammicus (Valenciennes 1832). 18 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 5 records from A new species of snook, Centropomus (Teleostei: Centropomidae), from northern South America, with notes on the geographic distribution of other species of the genus. 606 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 21 records from Tyrannosaurus And Torosaurus, Maestrichtian Dinosaurs From Trans-Pecos, Texas. 2 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 4 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 76 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 34 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 380 records from Wichita State University Collection. 3 records from Chemistry supports the identification of gender-specific reproductive tissue in Tyrannosaurus rex. 4 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 3 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 320 records from pbzt_insect_biodiversity. 4 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 23 records from Metagenetic analysis of copepod community in the tropical and subtropical Pacific. 28 records from NZCS Upper Tapanahony Expedition 1991. 9 records from A new subspecies of Delias clathrata Rothschild, 1904 and records of other Delias species occurring on Mount Hagen, Papua New Guinea (Lepidoptera: Pieridae, Pierinae). 1 records from Oppia nitens. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 3 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 1 records from Tanzanian Vertebrate Collection. 40 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 603 records from Fossil (NSMK-FO). 2 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 7 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 4 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 4 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 1361 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 5 records from Three new species of Oxypoda from Spain, Armenia, and Ukraine with notes on the fauna of Armenia (Coleoptera: Staphylinidae: Aleocharinae). 58 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 79 records from The Calliphoridae (Diptera) of Armenia. 15 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 28 records from Korean Plant Virus Database. 5 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 10 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 30 records from Herbarium Senckenbergianum (FR) - Protista. 358 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P9. 250 records from Colección de helechos de la FML. 3 records from Zoology in the Middle East. 4 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 1000 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 32 records from Coleção de Nematoda do Museu Nacional - UFRJ. 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 6 records from The bee genus Caenaugochlora (Hymenoptera, Apoidea) and its constituent subgenera, with new species of Caenaugochlora s. str. from Ecuador. 1 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 3 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 51 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 3740 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 5 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 2 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 2135 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 119 records from Fungi specimens of Saitama Museum of Natural History. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 26 records from New acoustic and molecular data shed light on the poorly known Amazonian frog Adenomera simonstuarti (Leptodactylidae): implications for distribution and conservation. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 5 records from Thalassironus filiformis sp. nov. (Nematoda, Enoplida) from the South China Sea. 1 records from Oribates fusifer. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 13 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 7 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 57 records from Nemertini - SMF. 1 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 362 records from Mammalian Specimens of the Yamagata Prefectural Museum. 89 records from Bird specimens of Ryukyu University Museum (Fujukan). 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 731 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 1 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 3 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 8 records from New and little-known crickets from Southern Guangxi, China (Orthoptera: Grylloidea: Gryllidae: Phalangopsidae; Trigonidiidae). 67 records from Weevils of Poland. 2 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 977 records from Habitat and host related variation in sponge bacterial communities in Indonesian coral reefs and marine lakes. 10 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 1 records from Arachnida of Costa Rica (INBio). 18 records from Revision of the Melanogaster jaroslavensis group (Diptera: Syrphidae), with description of a new species from Afghanistan. 24 records from Seawater carbonate chemistry, nutrients, and Calcidiscus leptoporus (strain RCC1135) growth rate and calcification rate during experiments, 2012. 16 records from Occurrence of some antimalarial plants from Cameroon. 1 records from A new species of Mesochra (Copepoda: Harpacticoida: Canthocamptidae) from a coastal system of northern Colombia with a key to the American species. 9 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 1 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 1 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 12 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 4 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 3 records from Galathea II, Danish Deep Sea Expedition 1950-52. 1 records from The Crushing Bite of Tyrannosaurids. 657 records from NCSM Non-molluscan Invertebrates Collection. 2 records from Antarctic Parborlasia corrugatus. 3162 records from The AAU Herbarium Database. 732 records from DSMZ Collection of Plant Viruses. 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 7 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 2 records from Newly reported genus Batracomorphus Lewis (Hemiptera: Cicadellidae: Iassinae) from Pakistan with description of a new species. 4 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 432 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 37 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 488 records from Colecção Entomológica do Museu de História Natural de Maputo. 1 records from A new species of Umanella Gauld (Hymenoptera, Ichneumonidae) from Ecuador. 18 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 1227 records from Collection Polychaeta - ZSRO. 48844 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 21 records from Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia. 15 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 1 records from A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran. 13 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 147 (N.S) n° 40 (2), 2012 - Données faune. 26 records from Revalidation and taxonomic revision of Teloneria Aczél (Diptera, Neriidae), with description of two new species. 38 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 1 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 1 records from Description of a new whiteflyı Pealius satakshiae Dubey (Hemiptera: Aleyrodidae) ı infesting Quercus leucotrichophora (Fagaceae) in the Western Himalayaı India. 3 records from A new species of phlebotomine sandfly, Pintomyia (Pifanomyia) duckei (Diptera: Psychodidae) from Manaus, State of Amazonas, Brazil. 22575 records from Living plant collection of Meise Botanic Garden. 14 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 443 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 30 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 35 records from Gunma Museum of Natural History, Fungi Specimen. 13977 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 5583 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 14 records from Eight new species of Ptenidiini and Discheramocephalini (Coleoptera: Ptiliidae) from Ecuador. 23 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 11 records from Revision of the non-marine centric diatom flora (Bacillariophyta) of the sub-Antarctic Campbell Island (southern Pacific Ocean) with the descriptions of five new species. 21 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 27192 records from Plant specimens of Horaiji-san Museum of Natural History Kichi T. collection. 3 records from Lectotypification of three species of Silene sect. Italicae (Rohrb.) Schischk. (Caryophyllaceae). 3 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 5 records from Revision of Chimarrogale (Lipotyphla: Soricidae) from Vietnam with comments on taxonomy and biogeography of Asiatic water shrews. 1 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 2925 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 65 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 11 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 25032 records from UWFC Ichthyology Collection. 1606 records from Auburn University Museum of Natural History Invertebrates. 17 records from Theropods of the Judith River Formation of dinosaur Provincial Park, Alberta, Canada. 8 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 402 records from The ultor - group of the genus Dolichogenidea Viereck (Hymenoptera, Braconidae, Microgastrinae) from China with the descriptions of thirty-nine new species. 57 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 4715 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 5 records from A new genus and two new species of soft scale insect (Sternorrhyncha, Coccoidea, Coccidae) from Africa. 10804 records from CUMV Fish Collection. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 609 records from Données ONF faune-flore-fonge. 2116 records from Collection entomologique Pierre Lachiver. 1 records from A taxonomic study on the Bornean and Philippines Sword-tailed Crickets in the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trgonidiidae; Trigonidiinae). 3 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 29 records from Stenus maculifer CAMERON: eine Büchse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 1229 records from University of Tennessee Fungal Herbarium. 109943 records from University of Michigan Museum of Zoology, Division of Mollusks. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 1 records from Setaphyes elenae sp. nov., a new species of mud dragon (Kinorhyncha: Allomalorhagida) from Skagerrak (north-eastern Atlantic Ocean). 3 records from Review of the fossil record of Bittacomorphinae (Diptera: Ptychopteridae). 86 records from Données opportunistes. 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 4 records from DASSH Data Archive Centre Academic Surveys. 75 records from Annotated type-catalogue of Brachyura (Crustacea, Decapoda) of the Muséum national d’Histoire naturelle, Paris. Part II. Gecarcinidae and Grapsidae (Thoracotremata, Grapsoidea), with an Appendix of pre- 1900 collectors. 20 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 3 records from A new species of Streblospio (Polychaeta: Spionidae) from the northern Adriatic Sea (Mediterranean Sea). 8 records from Two amazing new species of treehoppers (Hemiptera: Membracidae) from Colombia: Calloconophora estellae sp. nov. and Problematode robertoi sp. nov.. 1 records from A new flower fly species of Cepa Thompson & Vockeroth (Diptera: Syrphidae) from the Valdivian evergreen forest hotspot, Chile. 155 records from Foreign plant germplasm collections in Ghana. 1 records from Description of Pseudosteineria longisetis sp. n. from northeastern Brazil with a review of the genus Pseudosteineria Wieser, 1956 (Nematoda: Xyalidae). 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 18 records from Fauna Species of Camiguin Island, Philippines. 35 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 105 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 15491 records from Collection Pisces SMF. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 6 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 3 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 120716 records from Microbial biogeography of 925 geothermal springs in New Zealand. 7813 records from MEXU/Tipos de plantas vasculares. 1 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 26 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 3 records from The Genus Pseudopomyza (Diptera: Nerioidea) in Tasmania, with Description of a New Species. 22 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 9 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 4 records from One new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae Meconematinae) from Guangxi, China. 222 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 13 records from SPC CoFish Invertebrates Observations Niue 2005. 34 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 5 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 191 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 203 records from Estonian Nature Observations Database. 3 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 26 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 8505 records from Botanical Museum, Copenhagen, Mycology Herbarium. 2 records from A new species of Seira (Collembola: Entomobryidae) from northeastern Brazil. 6401 records from NCSM Mammals Collection. 14 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 4404 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 5027 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 150 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 10 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 1 records from On the Chilopoda from Turkey. 9 records from A contribution to taxonomy of the superfamily Grylloidea Laicharting from Yunnan, China (Orthoptera: Grylloidea). 1 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 3 records from Nouvelles fourmis de Madagascar.. 1 records from Fife Nature Records Centre combined dataset. 99 records from CHAS Botany Collection (Arctos). 10 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 2 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 41 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 12 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 51 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 7 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 27 records from Review of Neocynorta Roewerı 1915 with two new generic synonymies (Opiliones: Gonyleptoidea: Cosmetidae). 1032 records from Odonata de Veracruz. 309 records from Chapter 7: Linnaean Plant Names and their Types (part T). 296 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 647 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 500 records from Coleccion de helechos de la FML. 513 records from Quoll sightings register for Nth QLD. 8 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 55 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 1 records from A new species of Ischyomius from Venezuela (Coleoptera, Tenebrionoidea, Pythidae) with a revised key to world species. 27754 records from University of Florida Invertebrate Paleontology. 6 records from Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae). 120 records from Review, cladistic analysis and biogeography of Nezara Amyot & Serville (Hemiptera: Pentatomidae). 3 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 36 records from A revision of the systematics and distribution of the damselfly genus Prodasineura Cowley, 1934 (Odonata: Zygoptera: Platycnemididae) in Vietnam with description of two new species. 3 records from The spider genus Hersilia in Thailand, with descriptions of two new species (Araneae, Hersiliidae). 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 1 records from Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India. 10 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Description of Ghatiana, a new genus of freshwater crab, with two new species and a new species of Gubernatoriana (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from the Western Ghat Mountains, India. 1 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 122 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 32 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 72 records from University of Kentucky Insect Collection. 9 records from Six freshwater microturbellarian species (Platyhelminthes) in permanent wetlands of the Coastal Plain of southern Brazil: new records, abundance, and distribution. 12067 records from UAM Bird Collection (Arctos). 1 records from A new species of Eremias (Squamata: Lacertidae) from the arid mountains of Pakistan. 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 4 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica Tapachula). 11 records from Barsine wangi, a new species from Guangdong, southern China (Lepidoptera, Erebidae, Arctiinae). 6 records from Validation of Owenia vieitezi Díaz-Díaz, Parapar & Moreira, a polychaete from the coast of Venezuela (Annelida: Oweniidae). 6 records from A new species of salamander of the genus Hynobius (Amphibia, Caudata, Hynobiidae) from South Korea. 8 records from Records of Wenchengia (Lamiaceae) from Vietnam. 4 records from A survey of East Palaearctic Gnaphosidae (Araneae). 10. Three new Gnaphosa species from the Dzhungarian Alatau Mountains (Eastern Kazakhstan). 1 records from Microbes in drinking water and biofilms (18S rDNA amplicon study). 437 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 13 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 10 records from Lectotype designations, taxonomic notes and new synonymy in some species of the bee genus Centris Fabricius, 1804 described by William Henry Fox (Hymenoptera: Apidae). 9 records from Discovery of Raphidioptera (Insecta: Neuropterida) in Xizang, China, with description of a new species of Inocellia Schneider. 7 records from New species of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae: Meconematini) from Sichuan, China. 445 records from Algae collection. 237 records from Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions. 1 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 15 records from A key to the East Palaearctic and Oriental species of the genus Rhysipolis Foerster, and the first host records of Rhysipolis longicaudatus Belokobylskij (Hymenoptera: Braconidae: Rhysipolinae). 2 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 24039 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 15 records from Guinea-Bissau Herpetological Collection - IICT. 1 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 6 records from Fungal community across a tropical forest disturbance gradient. 84 records from Synopsis of the bee genus Thygater Holmberg 1884 (Hymenoptera, Apidae) in the Brazilian state of Minas Gerais, with the description of a new species and a key to all Brazilian species. 1 records from A new species of Schindler's fish (Teleostei: Gobiidae: Schindleria) from the Malay Archipelago (Southeast Asia), with notes on the caudal fin complex of Schindleria. 2 records from Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin. 434 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 4 records from Four new monoraphid diatom species (Bacillariophyta, Achnanthaceae) from the Maritime Antarctic Region. 1 records from On the Chilopoda from Turkey. 1 records from About the enigmatic Dichotrachelus valesiacus Stierlin, 1878 (Coleoptera, Curculionidae, Cyclominae). 40 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 107 records from The Stephanidae (Hymenoptera) of Mexico, with description of six new species and key to western Foenatopus Smith. 1 records from A new garden eel, Heteroconger fugax (Congridae: Heterocongrinae), from the northwestern Pacific Ocean. 13 records from The fast-running flies (Diptera, Hybotidae, Tachydromiinae) of Singapore and adjacent regions. 7 records from Contributions to the millipede genus Nepalella Shear, 1979 from China, with four new species and first results on phylogeny based on DNA-barcoding (Diplopoda, Chordeumatida, Megalotylidae). 21 records from Revision of the Palaearctic and Oriental species of the genus Oides Weber, 1801 (Coleoptera: Chrysomelidae: Galerucinae). 7 records from The pliomerid trilobite Ibexaspis and related new genera, with species from the Early Ordovician (Floian; Tulean, Blackhillsian) of the Great Basin, western USA. 5 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 25 records from Four new and one newly recorded species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Vietnam, with redescription of the little known species Diduga haematomiformis van Eecke, 1920. 4588 records from Bird database Natuurmuseum Brabant. 7 records from of patch-nosed snake (Colubridae: Salvadora Baird and Girard, 1853) from Oaxaca, Mexico. 116 records from Amphibiens et Reptiles de France métropolitaine (Enquête 1). 2 records from Redescription of Lernaeenicus stromatei Gnanamuthu, 1953 (Copepoda: Siphonostomatoida: Pennellidae) infesting the Black Pomfret Parastromateus niger (Bloch) from Indian waters. 89 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 135 records from VMNH SVDM Invertebrate Paleontology. 118 records from Chapter 7: Linnaean Plant Names and their Types (part I). 976 records from Les spermaphytes de l'Herbier du Centre National de Floristique de Côte d'Ivoire: deuxième partie.. 12 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 4 records from The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960. 240 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 6627 records from ATCC Fungi Collection Catalog. 50 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 1 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 42 records from New records of chalcidid (Hymenoptera: Chalcididae) pupal parasitoids from India. 1 records from Two atypical new species of the genus Sectonema Thorne, 1930 (Nematoda, Dorylaimida, Aporcelaimidae) from Vietnam. 7 records from Dima spicata Schimmel, 1999 (Elateridae: Dimini), a morphologically remarkable species endemic to China. 5 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 9 records from Taxonomic studies on the genus Orancistrocerus van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 18 records from Amphicnemis rigiketit sp. nov. from Sarawak, with notes on Amphicnemis remiger Laidlaw, 1912 (Odonata: Zygoptera: Coenagrionidae). 447 records from Coleoptera Collection. 206 records from Зимние маршрутные учеты. 12 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 1 records from Nothrus peltifer. 9 records from Four new species and new records of Manota (Diptera: Mycetophilidae) from Sulawesi, Indonesia. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en el Parque Provincial Salto Encantado (Guller et al.a, marzo 1997). 1912 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 45 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 2 records from A unique new genus and species of the phyline plant bug tribe Hallodapini from the Philippines and Thailand (Hemiptera: Heteroptera: Miridae: Phylinae: Hallodapini). 6 records from Description of a new species of Ochraethes Chevrolat, 1860, redescription of Plocaederus mirim Martins and Monné, 2002, and new geographical records for Plocaederus Dejean, 1835 (Coleoptera, Cerambycidae, Cerambycinae). 74 records from Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes. 17684 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 1 records from Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia. 3 records from Welsh Invertebrate Database (WID). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 140 records from An annotated catalogue of Elachistinae of the World (Lepidoptera: Gelechioidea: Elachistidae). 7 records from Taxonomic revision of the microleafhopper genus Limassolla Dlabola from Korea (Hemiptrea: Cicadellidae: Typhlocybinae). 1 records from Nouvelles fourmis d'Afrique.. 3 records from Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 4 records from Polyphasic classification of Nonomuraea strains isolated from the Karakum Desert and description of Nonomuraea deserti sp. nov., Nonomuraea diastatica sp. nov., Nonomuraea longispora sp. nov. and Nonomuraea mesophila sp. nov.. 11 records from Four New Bat Species (Rhinolophus hildebrandtii Complex) Reflect Plio-Pleistocene Divergence of Dwarfs and Giants across an Afromontane Archipelago. 23 records from First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand. 2 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 1 records from Revisiting Gryposuchus jessei Gürich, 1912 (Crocodylia: Gavialoidea): specimen description and comments on the genus. 37 records from Miscophus Jurine, 1807 (Hymenoptera, Crabronidae) in Central, Northern, and Eastern Europe. 3 records from Meschia zoui sp. nov., first representative of the family Meschiidae from China (Hemiptera: Heteroptera: Lygaeoidea). 3 records from Genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) from Laos, with descriptions of five new species. 1093 records from Systematic studies on Pseudomyrmex acacia-ants (Hymenoptera: Formicidae: Pseudomyrmecinae). 6 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 86 records from Données naturalistes de Pierre FRAPA. 1169 records from Collection Crustacea ZMG. 1 records from Revision of Chinese mainland Hybovalgus Kolbe, 1904, with description of a new species, and Excisivalgus Endrödi, 1952 reduced to synonymy with Hybovalgus (Coleoptera: Scarabaeidae). 1500 records from Fish specimens of Takatsuki Nature Museum (Aquapia Akutagawa). 10098 records from Araneae Collection. 1 records from A fossil caddisfly (Insecta: Trichoptera) from the Eocene of Colorado. 12 records from Redescription of Inglisia vitrea Cockerell (Hemiptera, Coccidae) and its transfer to the genus Pseudokermes Cockerell. 23 records from First record of a native Atomaria S, 1829 (Coleoptera: Cryptophagidae) from the Neotropical Region. 223 records from MfN - Fossil invertebrates IIa. 2 records from Département_du_Var_2017_12_18. 566 records from Vertebrados registrados durante el muestreo de tigrillos melánicos en el Valle del Cauca. 9 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 5 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 11619 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 16 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 4 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 32737 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 122 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 6 records from A revision of Holothuria (Halodeima) kefersteinii (Selenka, 1867) and the revival of Holothuria inornata Semper, 1868 from sea cucumbers collected in Mexico and Central America. 24536 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 11 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 2 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 11 records from Annales de la Société entomologique de France [1832- ]. 156 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 2 records from Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber. 173415 records from Hymenoptera specimen database of Kyushu University. 1 records from Lemyra persephone, a new autumnal species from Yunnan, southwestern China (Lepidoptera, Erebidae, Arctiinae). 49568 records from Finnish Floristic Database (Literature Sources). 174 records from The Myriapoda Collection of the National Museum of Nature and Science. 27 records from Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 2 records from A new species of anole from Parque Nacional Volcán Arenal, Costa Rica (Reptilia, Squamata, Dactyloidae: Norops). 2 records from Inventaire avifaune. 54663 records from iNaturalist Research-grade Observations. 8406 records from Conservatoire Botanique Pierre Fabre. 4 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 1309 records from Mongolian Plant (MMNH-PL). 6 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 27 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 13 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 46 records from A check list of the Chinese Zeugophorinae (Coleoptera: Megalopodidae), with new synonym, new record and two new species of subgenus Pedrillia from China. 80 records from An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea). 64 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 25 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 2 records from Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China. 4 records from A new species of Lamprodila (Ovalisia Kerremans, 1900) (Coleoptera: Buprestidae) from Sulawesi, Indonesia. 10102 records from Régénération naturelle de ligneux du Sénégal. 2 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 10 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 1095 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 6 records from données arachnologiques de CARR David. 13 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 16 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 1594 records from Musée Vert ornithology collection. 419 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 812 records from Espèces végétales inventoriées dans les formations et strates de la forêt classée de Missahoe au Togo en 2017.. 36 records from Review of Chinese species of the Oxylipeurus - complex (Phthiraptera: Philopteridae), with descriptions of two new genera and five new species. 6093 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 61798 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 44 records from Estudio ecológico y genético de las poblaciones de Rhizophora mangle en México. 2 records from Porifera ZMK. 1 records from Nothrus furcatus. 31 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 4 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 3 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 543 records from Collection Berlie. 12 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 5704 records from marine sediment metagenome Raw sequence reads. 12 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 56 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 1 records from Oribates flammula. 171 records from JCT AVH data. 12260 records from University of Tennessee Bryophyte Herbarium. 3307 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 9726 records from Paleobotany Specimens. 83 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 106100 records from Fish (NSMK-PI). 2 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 5 records from Collection Myriapoda - SNSD. 1 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 7 records from A new large-bodied, rupicolous Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) allied to Cnemaspis heteropholis Bauer, 2002 from the Central Western Ghats of Karnataka, India. 9 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 3 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 1 records from A new species of Stenampyx Karsch, 1890 from East Africa (Orthoptera: Tettigoniidae, Pseudophyllinae, Phyllomimini) - evidence of a former connection of West-Central and East African forests. 4 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 2 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 8 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 5 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 1535 records from DAR AVH data. 1 records from A new species of Proneuronema (Neuroptera: Hemerobiidae) from late Eocene Rovno amber. 1 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 2 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 1 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 1050 records from DBL_Life. 23 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 3178 records from Newfoundland sediment pyrosequencing. 3 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 90 records from MiSeq 16S rRNA gene (archaeal 16S rRNA gene) sequences of 4 SCS sediments. 4682 records from Fungal diversity in Sanya mangrove sediments, China. 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 90 records from Thrips (Thysanoptera) in Norway. 2 records from A new species of Homo from the Late Pleistocene of the Philippines. 4065 records from Microbial community in permeable intertidal sediment. 1 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 4 records from Description of Coladenia simianensis sp. nov. (Lepidoptera: Hesperiidae) from China, with an annotated checklist of the genus Coladenia Moore, 1881. 1 records from Antarctic Euphausiacea occurrence data from ITALICA 2000 Expedition. 63 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 59 records from Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean). 2 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 11856 records from NHMO DNA Bank Vascular plants collection. 11991 records from HPL - Herbário do Jardim Botânico Plantarum. 2 records from Observations et collection de Coléoptères d'Alain Sadorge. 8 records from Notes on the spider genus Segestria Latreille, 1804 (Araneae: Segestriidae) in the East Palaearctic with description of three new species. 56413 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 31 records from Scilla hakkariensis, sp. nov. (Asparagaceae: Scilloideae): a new species of Scilla L. from Hakkari (eastern Anatolia). 114 records from Faunistic review of Tetratomidae and Melandryidae (Coleoptera: Tenebrionoidea) in Lithuania with an annotated checklist of the species. 189 records from Insect specimens of Mie Prefectural Museum. 1 records from Description of a second species of the genus Moronius Grossi & Vaz-de-Mello, 2015 (Coleoptera: Scarabaeidae: Rutelinae: Rutelini). 1479 records from TTRS Ornithology. 762 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 4 records from Description of a new alpheid shrimp, Automate isabelae sp. nov. (Decapoda, Caridea, Alpheidae) found in fish stomach contents of the lane snapper Lutjanus synagris (Linnaeus, 1758), from the west coast of Florida, Gulf of Mexico. 677 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 7245 records from Sammmlung Ule Brasilien Herbarium Hamburgense HBG. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 20 records from El género Bursera en México. Parte II. 15 records from PSUZC-Mammal Collection. 1 records from Two new marine species of Cocconeis (Bacillariophyceae) from the west coast of Sweden. 100 records from Canadian National Collection of Insects. 2 records from Données d'oiseaux. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1 records from Record of genus Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Conocephalinae; Copiphorini) and description of one new species from India. 14 records from Description of the female of Labena madoricola González-Moreno & Bordera, 2015 (Hymenoptera, Ichneumonidae, Labeninae), with new records of Labena species from Mexico. 2 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 19 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 10 records from African Spilogona Schnabl: morphology of the male terminalia and description of a new species (Diptera: Muscidae). 90 records from Herbario MAIA, colección de Ericas del INIA-CIFOR. 5638 records from Estación Biológica D
Keywords: GBIF; biodiversity; species occurrences